A polyamide reverse osmosis composite membrane for efficiently removing endocrine disruptors and a preparation method thereof
By using heavy nitrogen-hydraulic-puppet-reacting branches and polyphenol small molecules on the surface of polyamide reverse osmosis composite membrane to solve the problem of low EDCS removal efficiency in the existing technology, and achieve efficient removal of EDCS to remove EDCS The effect, while maintaining water permeability.
Patent Information
- Application Number
- CN202411506800.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-28
AI Technical Summary
The existing polyamide reverse osmosis composite membranes are not ideal for neutral, low molecular weight and polar endocrine disturbances (EDCs), and the interception rate is usually less than 50%. At the same time, water permeability is easily lost in the process of improving the removal efficiency.
Using the surface-to-be-position modification method of heavy nitride-coupel-reactive reaction, on the surface of the polyamide nanosangular surface, the co-priced covarcation of polyamide-branches and polyphenol small molecules, repair the inherent defects on the surface of the membrane, improve the pro-kiss kinship Water properties and water transmission paths form a dense hydrological layer to enhance removal efficiency.
The removal rate of EDCS is significantly increased by polyamide reverse osmosis membrane, reaching 87%-99%. At the same time, it maintains high water permeability and is suitable for high-efficiency removal of small molecular microne pollutants in water.
Smart Images

Figure CN119015910B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of membrane separation material preparation, and particularly relates to a polyamide reverse osmosis composite membrane for efficiently removing endocrine disruptors and a preparation method thereof. Background Art
[0002] The ubiquitous presence and persistence of new small-molecule organic micropollutants, represented by pharmaceutically active compounds, endocrine disrupting compounds and disinfection by-products, in the aquatic environment has caused serious concerns about drinking water safety and public health. In particular, endocrine disrupting compounds (EDCs) can have strong endocrine disrupting effects even at trace concentrations, posing a significant threat to human health. Therefore, the effective removal of EDCs in reclaimed water has become a new challenge in global water systems. Membrane separation technology, represented by reverse osmosis, has the characteristics of separation, concentration, purification and refinement, and has been widely used in the fields of wastewater reuse and deep drinking water treatment. Existing polyamide reverse osmosis composite membranes have excellent salt / water permeability selectivity (such as NaCl retention rate higher than 99%), but many studies have found that their removal efficiency for neutral, low molecular weight and polar EDCs is not ideal, and the EDC retention rate is usually less than 50% (Environ. Sci. Technol. Lett. 2022, 9, 247-257; Angew. Chem. Int. Ed. 2024, 63, e202402509; J. Membr. Sci. 2024, 461, 132628; J. Membr. Sci. 2020, 595, 117577; Chemosphere 2018, 200, 80-85; Water Res. 2019, 148,535-545).
[0003] The polyamide reverse osmosis membrane is a composite structure consisting of a non-woven fabric, an ultrafiltration porous support layer and a polyamide dense layer, wherein the polyamide dense layer is prepared by the interfacial polymerization reaction of m-phenylenediamine and trimesoyl chloride on an ultrafiltration polymer membrane. The structure and properties of the polyamide dense layer determine the ability of the composite membrane to remove organic micropollutants and water permeability. On the one hand, the fully aromatic polyamide chemistry gives the polyamide reverse osmosis composite membrane poor hydrophilicity, resulting in hydrophobic interactions between its surface and EDCs; on the other hand, interfacial degassing during the formation of the polyamide dense layer leads to nano-defects in the structure of the polyamide dense layer. These inherent defects will further reduce the removal efficiency of EDCs (Environ. Sci. Technol. Lett.2022, 9, 247-257; Water Res. 2021, 203, 117520; Environ. Sci. Technol. 2020,54, 3559-3569; Nat. Rev. Mater. 2016, 1, 16018). Therefore, how to regulate the structural characteristics (such as effective pore size, pore size distribution and surface defects) and surface chemical properties (roughness, hydrophilicity and polarity, etc.) of polyamide nanomembranes is the key to designing polyamide nanomembranes that efficiently remove micropollutants.
[0004] Based on size screening and hydrophobic interaction separation mechanism, constructing nanostructures (Environ. Sci.Technol. Lett. 2022, 9, 247) and surface modification (Desalination 2023, 565, 116861) are two main strategies to improve the EDCs retention rate of polyamide nanomembranes. Regulating the interfacial polymerization formula (Environ. Sci. Technol. 2024, 58, 9416-9429), constructing an intermediate layer (patent CN 118045495 A) and incorporating nanoporous materials (Environ. Sci. Technol. 2020, 54, 7619-7628) to increase the crosslinking degree of the polyamide dense layer and increase the density of the polyamide nanomembrane can significantly improve the solute retention rate of the reverse osmosis membrane. However, due to the restrictive effect between membrane permeability and selectivity, increasing the density of the reverse osmosis membrane retention layer will inevitably lose the water permeability of the membrane. Surface coating based on non-covalent bonds and in-situ surface grafting based on chemical bonds can give the membrane surface the desired polymer or functional molecules to regulate the surface chemical properties and structure of the polyamide nanomembrane. For example, by coating the surface of commercial NF 90 membrane with polydopamine polymer coating, its retention rate of hydrophobic EDCs can be increased by 29%-42% (Environ. Sci. Technol. Lett. 2016, 3,332-338); by in-situ grafting of acrylic polymer on the surface of commercial reverse osmosis membrane FT 30 (J. Membr. Sci. 2024,703, 122810), its EDCs retention rate can be increased to 98.4%. Although these surface modification methods can significantly change the surface chemical properties (hydrophilicity and polarity) of polyamide nanomembranes, weaken the hydrophobic interaction between these organic micropollutants and the membrane surface, and improve the EDCs removal rate, the modified layer introduced on the membrane surface will not only block the pores on the surface of the nanomembrane, but also increase the mass transfer resistance, resulting in the sacrifice of permeability. Therefore, there is an urgent need to explore more effective modification strategies that can not only repair the inherent defects of the polyamide nanomembrane structure while improving the hydrophilicity of the membrane surface and reducing the hydrophobic effect, but also do not increase additional mass transfer resistance, so as to prepare a reverse osmosis composite membrane with excellent neutral or hydrophobic small molecule micropollutants removal efficiency without sacrificing its water permeability. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a polyamide reverse osmosis composite membrane for efficient removal of EDCs and a preparation method thereof. The present invention proposes a surface in-situ modification method based on "diazotization-coupling reaction" to in-situ covalently graft polyamide-amine dendritic macromolecules and polyphenol small molecules ( Figure 1). The dendritic macromolecules with regular pore structure can not only repair the inherent defects of the surface of the polyamide nanomembrane, strengthen the size screening effect, and improve the EDCs retention rate, but also the porous layer of the dendritic macromolecules can optimize the water transmission path on the membrane surface; in addition, the grafted hydrophilic polyphenol small molecules help to form a dense hydration layer on the membrane surface, which not only weakens the hydrophobic interaction between the small molecule neutral or hydrophobic organic micropollutants and the membrane surface, further improves its EDCs removal rate, but also enhances water permeability. Therefore, the modified polyamide reverse osmosis membrane of the present invention has excellent neutral or hydrophobic EDCs removal ability and high water permeability, and is suitable for the efficient removal of small molecule micropollutants in water.
[0006] The invention provides a polyamide reverse osmosis composite membrane for efficiently removing endocrine disruptors. The polyamide reverse osmosis composite membrane comprises a polysulfone ultrafiltration base membrane and a polyamide dense layer modified by a diazotization-coupling reaction. The polyamide reverse osmosis composite membrane has a NaCl rejection rate of 99.23%-99.65%, an endocrine disruptor rejection rate of 87%-99%, and a water permeation flux of 3.92-4.23 L m -2 h -1 bar -1 , which is far superior to the virgin polyamide reverse osmosis membrane (the retention rate of endocrine disruptors is 43%-63%).
[0007] The present invention also provides a polyamide reverse osmosis composite membrane for efficiently removing endocrine disruptors, comprising the following steps: (1) coating a polyamine aqueous solution on a polysulfone ultrafiltration base membrane, and then immersing it in an acyl chloride organic solution, and obtaining a nascent polyamide dense layer after heat treatment; (2) immersing the prepared nascent polyamide dense layer in an acidic aqueous solution of polyamide-amine dendritic macromolecules, and then immersing it in an acidic aqueous solution of sodium nitrite to induce a diazotization reaction; (3) subsequently immersing it in an alkaline aqueous solution of polyphenols, and covalently grafting polyphenol small molecules on the surface of the polyamide dense layer through a diazotization-coupling reaction to obtain the polyamide reverse osmosis composite membrane.
[0008] Further, the method comprises the following steps: (1) coating a polyamine aqueous solution on a polysulfone ultrafiltration base membrane, removing the aqueous phase on the base membrane after 2-5 minutes; then immersing it in an acyl chloride organic phase solution for 30-120 seconds, and then removing the excess organic phase; placing it in a vacuum drying oven, and further crosslinking it for 2-10 minutes to obtain a nascent polyamide dense layer; (2) immersing the prepared nascent polyamide dense layer in an acidic aqueous solution of polyamide-amine dendritic macromolecules for 5-30 minutes, and removing the excess solution; then immersing it in an acidic aqueous solution of sodium nitrite for 1-10 minutes, allowing it to stand to induce a diazotization reaction, and removing the excess solution; (3) then immersing it in an alkaline aqueous solution of polyphenols for 1-10 minutes, covalently grafting polyphenol small molecules on the surface of the polyamide dense layer through a diazotization-coupling reaction, and removing the excess solution to obtain the polyamide reverse osmosis composite membrane.
[0009] Furthermore, the polyamine aqueous phase solution in step (1) is composed of 1.5-4.0 w / v% m-phenylenediamine, 1.1-2.3 w / v% camphorsulfonic acid, 0.65-1.1 w / v% triethylamine and 0.01 w / v% sodium hydroxide; in the acyl chloride organic phase solution, the organic acyl chloride is 0.05-0.4 w / v% trimesoyl chloride, and the organic solvent is one of n-hexane, n-heptane, n-decane or isopar-G.
[0010] Further, the nascent polyamide dense layer prepared in step (1) is immersed in a polyamide-amine dendrimer solution with a concentration of 0.01-1.0 w / v% and a solution pH of 1-3; the polyamide-amine dendrimer is composed of an end-capping molecule of aniline and a branching structure of aliphatic polyamide; the polyamide-amine dendrimer is one of 32- / 64- / 128-aniline-terminated polyamide-amine dendrimers, and its structural formula is as follows:
[0011]
[0012] 3,2-aniline-terminated polyamidoamine dendrimers
[0013]
[0014] 6,4-aniline-terminated polyamidoamine dendrimers
[0015]
[0016] 128-aniline-terminated polyamidoamine dendrimers
[0017] Furthermore, the concentration of sodium nitrite in step (2) is 0.5-3.0 w / v%, and the solution pH is 1.0-3.0; the concentration of the polyphenol aqueous solution in step (3) is 0.1-5.0 w / v%, and the solution pH is 8.5-9.5; and the polyphenol molecule is one of tannic acid, phloroglucinol or catechol.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] (1) The method of the present invention is simple to operate and easy to scale up. It repairs the defects of the polyamide nanostructure through in situ covalent grafting modification, and introduces a porous and hydrophilic modification layer to improve its pressure resistance and structural stability.
[0020] (2) The in-situ surface modification described in the present invention is to covalently graft the dendritic macromolecules with regular pore structure and the hydrophilic polyphenol small molecules through diazotization-coupling reaction. The hydrophilicity of the surface of the polyamide nanomembrane is improved, which not only improves its anti-pollution performance, but also the modified layer acts as a sacrificial layer, which can significantly improve its chlorine resistance.
[0021] (3) In the present invention, the dendritic macromolecules are covalently grafted onto the surface of the nascent polyamide nanomembrane through a diazotization-coupling reaction on the surface of the polyamide formed by interfacial polymerization. This can not only make up for the inherent structural defects of the surface of the polyamide nanomembrane and improve the salt retention rate and EDCs removal capacity of the polyamide membrane; but also, due to the porous structural characteristics of the dendritic macromolecules, the water transmission path can be optimized, and the water permeability of the modified polyamide membrane is slightly improved.
[0022] (4) The NaCl rejection rate of the nascent polyamide reverse osmosis membrane of the present invention is less than 98.1%, the EDCs rejection rate is 43%-63%, and the water permeation flux is 3.89-4.01 L m -2 h -1 bar -1 The modified polyamide reverse osmosis membrane prepared by the present invention has a NaCl rejection rate of 99.23%-99.65%, an EDCs rejection rate of 87%-99%, and a water permeation flux of 3.92-4.23 Lm -2 h -1 bar -1 . BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a schematic diagram of the chemical structure of the polyamide nanomembrane prepared in Example 2 of the present invention. As shown in the figure, aniline-terminated polyamide-amine dendrimers with regular pore structure and tannic acid are grafted on the surface of the polyamide dense layer through azo bonds (-N=N-).
[0024] Figure 2This is a transmission electron micrograph of the modified polyamide reverse osmosis membrane prepared in Example 2 of the present invention. The in-situ covalent grafting of dendritic macromolecules increases the porosity of the polyamide dense layer, reduces the volume mass density, and is beneficial to the improvement of the permeation flux.
[0025] Figure 3 This is a cross-sectional scanning electron microscope image of the modified polyamide reverse osmosis membrane prepared in Example 2 of the present invention. It can be seen from the image that the leaf-like structure of the polyamide dense layer has abundant nanopores inside.
[0026] Figure 4 This is a surface scanning electron microscope image of the modified polyamide reverse osmosis membrane prepared in Example 2 of the present invention. The nanoparticles on the leaf-like structure are grafted polyamide-amine dendritic macromolecules, which can not only make up for the structural defects but also improve the porosity of the dense layer.
[0027] Figure 5 The surface microscope image of the original polyamide reverse osmosis membrane prepared as a comparative example of the present invention shows that the original polyamide dense layer has a classic leaf-like structure.
[0028] Figure 6 This is a scanning electron microscope image of the cross section of the original polyamide reverse osmosis membrane prepared in the comparative example of the present invention. DETAILED DESCRIPTION
[0029] The present invention will be further described in detail below with reference to the embodiments of the present invention:
[0030] Example 1
[0031] (1) A polysulfone ultrafiltration membrane was coated with an aqueous solution of 3.25 w / v% m-phenylenediamine, 1.89 w / v% camphorsulfonic acid, 0.95 w / v% triethylamine, and 0.01 w / v% sodium hydroxide, and the membrane was allowed to stand for 2 min, after which the aqueous phase on the membrane was removed; the membrane was then coated with a 0.12 w / v% n-heptane solution of trimesoyl chloride for 1 min, and the excess oil phase was removed; the membrane was dried for 2 min;
[0032] (2) immersing the polyamide membrane prepared in step (1) in a 0.2 wt% solution of 3,2-aniline-terminated polyamide-amine dendrimer at pH 2, allowing the solution to stand for 30 min, and removing excess solution; then immersing the polyamide membrane in a 0.8 wt% solution of sodium nitrite at pH 2, allowing the solution to stand for 5 min, and removing excess solution;
[0033] (3) The polyamide membrane prepared in step (2) was immersed in a 2 wt % tannic acid solution with a pH of 8.5, allowed to stand for 5 min, excess solution was removed, and the membrane was placed in deionized water for testing.
[0034] Example 2
[0035] See also Figure 1-4 , a method for preparing a polyamide reverse osmosis membrane with high efficiency in removing EDCs, the specific steps are as follows:
[0036] (1) A polysulfone ultrafiltration membrane was coated with an aqueous solution of 3.25 w / v% m-phenylenediamine, 1.89 w / v% camphorsulfonic acid, 0.95 w / v% triethylamine, and 0.01 w / v% sodium hydroxide, and the membrane was allowed to stand for 2 min, after which the aqueous phase on the membrane was removed; the membrane was then coated with a 0.12 w / v% n-heptane solution of trimesoyl chloride for 1 min, and the excess oil phase was removed; the membrane was dried for 2 min;
[0037] (2) soaking the polyamide membrane prepared in step (1) in a 0.1 wt% solution of 64-aniline-terminated polyamide-amine dendrimer at pH 2, leaving it to stand for 30 min, and removing the excess solution; then soaking it in a 0.8 wt% sodium nitrite solution at pH 2, leaving it to stand for 5 min, and removing the excess solution;
[0038] (3) The polyamide membrane prepared in step (2) was immersed in a 2.5 wt% tannic acid solution with a pH of 8.5, allowed to stand for 5 minutes, excess solution was removed, and the membrane was placed in deionized water for testing.
[0039] Example 3
[0040] (1) A polysulfone ultrafiltration membrane was coated with an aqueous solution of 3.25 w / v% m-phenylenediamine, 1.89 w / v% camphorsulfonic acid, 0.95 w / v% triethylamine, and 0.01 w / v% sodium hydroxide, and the membrane was allowed to stand for 2 min, after which the aqueous phase on the membrane was removed; the membrane was then coated with a 0.12 w / v% n-heptane solution of trimesoyl chloride for 1 min, and the excess oil phase was removed; the membrane was dried for 2 min;
[0041] (2) soaking the polyamide membrane prepared in step (1) in a 0.1 wt% solution of 64-aniline-terminated polyamide-amine dendrimer at pH 2, leaving it to stand for 30 min, and removing the excess solution; then soaking it in a 0.8 wt% sodium nitrite solution at pH 2, leaving it to stand for 5 min, and removing the excess solution;
[0042] (3) The polyamide membrane prepared in step (2) was immersed in a 2.5 wt% catechol solution with a pH of 8.5, allowed to stand for 5 min, excess solution was removed, and the membrane was placed in deionized water for testing.
[0043] Example 4
[0044] (1) A polysulfone ultrafiltration membrane was coated with an aqueous solution of 3.25 w / v% m-phenylenediamine, 1.89 w / v% camphorsulfonic acid, 0.95 w / v% triethylamine, and 0.01 w / v% sodium hydroxide, and the membrane was allowed to stand for 2 min, after which the aqueous phase on the membrane was removed; the membrane was then coated with a 0.12 w / v% n-heptane solution of trimesoyl chloride for 1 min, and the excess oil phase was removed; the membrane was dried for 2 min;
[0045] (2) soaking the polyamide membrane prepared in step (1) in a 0.1 wt% solution of 64-aniline-terminated polyamide-amine dendrimer at pH 2, leaving it to stand for 30 min, and removing the excess solution; then soaking it in a 0.8 wt% sodium nitrite solution at pH 2, leaving it to stand for 5 min, and removing the excess solution;
[0046] (3) The polyamide membrane prepared in step (2) was immersed in a 2 wt % phloroglucinol aqueous solution with a pH of 8.5, allowed to stand for 5 min, excess solution was removed, and the membrane was placed in deionized water for testing.
[0047] Example 5
[0048] (1) A polysulfone ultrafiltration membrane was coated with an aqueous solution of 3.25 w / v% m-phenylenediamine, 1.89 w / v% camphorsulfonic acid, 0.95 w / v% triethylamine, and 0.01 w / v% sodium hydroxide, and the membrane was allowed to stand for 2 min, after which the aqueous phase on the membrane was removed; the membrane was then coated with a 0.12 w / v% n-heptane solution of trimesoyl chloride for 1 min, and the excess oil phase was removed; the membrane was dried for 2 min;
[0049] (2) soaking the polyamide membrane prepared in step (1) in a 0.08 wt% solution of 128-aniline-terminated polyamide-amine dendrimer at pH 2, leaving it to stand for 30 min, and removing the excess solution; then soaking it in a 0.8 wt% solution of sodium nitrite at pH 2, leaving it to stand for 5 min, and removing the excess solution;
[0050] (3) The polyamide membrane prepared in step (2) was immersed in a 2 wt % tannic acid solution with a pH of 8.5, allowed to stand for 5 min, excess solution was removed, and the membrane was placed in deionized water for testing.
[0051] Comparative Example
[0052] See also Figure 5 and 6 , the specific steps of the original polyamide reverse osmosis membrane prepared by comparison are as follows:
[0053] (1) A polysulfone ultrafiltration membrane was coated with an aqueous solution of 3.25 w / v% m-phenylenediamine, 2.3 w / v% camphorsulfonic acid, 1.1 w / v% triethylamine, and 0.01 w / v% sodium hydroxide, and the membrane was allowed to stand for 2 min, after which the aqueous phase on the membrane was removed;
[0054] (2) Apply 0.12 w / v% trimesoyl chloride in n-heptane solution for 1 min to remove excess oil phase; dry for 2 min and place in deionized water for testing.
[0055] The NaCl retention performance of the polyamide reverse osmosis composite membranes prepared in Examples 1-5 and the comparative example was tested. A laboratory-scale high-pressure reverse osmosis cross-flow device was used, and the effective area of the membrane pool was 12.88 cm 2 , the membrane was pre-pressed at an operating pressure of 15.5 bar until the membrane flux was stable, the water temperature was 25.0 °C, the cross-flow rate was 20 cm / s, and the NaCl concentration was 2000 ppm. The test results are shown in Table 1. The polyamide reverse osmosis composite membrane prepared in Examples 1, 2, 5 and the comparative example was tested for the retention performance of endocrine disruptors. Four representative endocrine disruptors (methyl paraben, ethyl paraben, benzyl paraben, bisphenol A, physicochemical properties are shown in Table 2) were selected with a concentration of 200 μg / L. The test conditions were an operating pressure of 15.5 bar, a test temperature of 25.0 °C, and a cross-flow rate of 20 cm / s. Pre-press for 12 h until the membrane surface adsorption reached saturation, and then start measuring. The EDCs concentration in the stock solution and the permeate was determined by high performance liquid chromatography tandem quadrupole mass spectrometry (LC-MS / MS, Thermo TSQ Quantum), and the test results are shown in Table 3.
[0056] Table 1 Desalination performance of polyamide reverse osmosis composite membranes prepared in Examples 1-5 and Comparative Examples
[0057]
[0058] Table 2 Physical and chemical properties of EDCs compounds selected for testing in the present invention
[0059]
[0060] Table 3 EDCs removal capacity of polyamide reverse osmosis membranes prepared in Examples 1, 2, 5 and Comparative Example
[0061] .
Claims
1. A method for preparing a polyamide reverse osmosis composite membrane for efficiently removing endocrine disruptors, characterized in that: The polyamide reverse osmosis composite membrane comprises a polysulfone ultrafiltration base membrane and a polyamide dense layer modified by diazotization-coupling reaction; the polyamide reverse osmosis composite membrane has a NaCl retention rate of 99.23%-99.65%, an endocrine disruptor retention rate of 87%-99%, and a water permeation flux of 3.92-4.23L m -2 h -1 bar -1 The preparation method comprises the following steps: (1) applying a polyamine aqueous solution to a polysulfone ultrafiltration base membrane, maintaining the solution for 2-5 minutes, and then removing excess aqueous phase on the base membrane; then immersing the base membrane in an acyl chloride organic solution for 30-120 seconds, and then removing excess oil phase solution; placing the base membrane in a vacuum drying oven, and further crosslinking the solution for 2-10 minutes to obtain a nascent polyamide dense layer; (2) immersing the prepared nascent polyamide dense layer in an acidic aqueous solution of polyamide-amine dendritic macromolecules with a pH of 1-3 and a concentration of 0.01-1.0 w / v% for 5-30 minutes, and removing excess solution; Then immerse it in an acidic aqueous solution of sodium nitrite for 1-10 minutes, let it stand to induce a diazotization reaction, and remove excess solution; (3) Subsequently, the polyamide is immersed in an alkaline aqueous solution of polyphenol for 1-10 minutes, and the polyphenol molecules are covalently grafted onto the surface of the polyamide dense layer through a diazotization-coupling reaction to obtain the polyamide reverse osmosis composite membrane; the polyamine aqueous phase solution described in step (1) is composed of 1.5-4.0 w / v% m-phenylenediamine, 1.1-2.3 w / v% camphorsulfonic acid, 0.65-1.1 w / v% triethylamine and 0.01 w / v% sodium hydroxide; the acyl chloride organic In the phase solution, the organic acyl chloride is 0.05-0.4w / v% of trimesoyl chloride, and the organic solvent is one of n-hexane, n-heptane, n-decane or isopar-G; the polyamide-amine dendrimer is composed of an end-capping molecule of aniline and a branched structure of aliphatic polyamide; the polyamide-amine dendrimer is one of the polyamide-amine dendrimers capped with 32- / 64- / 128-aniline, and its structural formula is as follows:
2. The method for preparing a polyamide reverse osmosis composite membrane for efficiently removing endocrine disruptors according to claim 1, characterized in that: The sodium nitrite concentration in step (2) is 0.5-3.0 w / v%, and the solution pH is 1.0-3.0; the polyphenol alkaline aqueous solution concentration in step (3) is 0.1-5.0 w / v%, and the solution pH is 8.5-9.0; the polyphenol molecule is one of tannic acid, phloroglucinol or catechol.
Citation Information
Patent Citations
Preparation method of polyamide reverse osmosis membrane with low volume density
CN113856482A